an-5an-1+6an-2=1

Simple and best practice solution for an-5an-1+6an-2=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for an-5an-1+6an-2=1 equation:


Simplifying
an + -5an + -1 + 6an + -2 = 1

Reorder the terms:
-1 + -2 + an + -5an + 6an = 1

Combine like terms: -1 + -2 = -3
-3 + an + -5an + 6an = 1

Combine like terms: an + -5an = -4an
-3 + -4an + 6an = 1

Combine like terms: -4an + 6an = 2an
-3 + 2an = 1

Solving
-3 + 2an = 1

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 2an = 1 + 3

Combine like terms: -3 + 3 = 0
0 + 2an = 1 + 3
2an = 1 + 3

Combine like terms: 1 + 3 = 4
2an = 4

Divide each side by '2n'.
a = 2n-1

Simplifying
a = 2n-1

See similar equations:

| 40xsomething+105-75=190 | | (1.04)n=13 | | 11+8r=29 | | 183+12-x+5=175 | | 45-(5x+8)=5(x+3)+x | | 1-3(2)=7 | | -(2x-4)=22 | | x-3(2)=7 | | 2x+8x-10=0 | | Ln(x)=0.21 | | lnx=0.21 | | 17y-7=9+2y | | 6x^2+5x+24=0 | | 7z-3=8z-9 | | 4x-20x=11 | | 4=5(x-2) | | 1/3*x^3*y^3=9 | | x^3+4x^2+8x+2=0 | | x^3-4x^2+8x+2=0 | | x^3-4x^2-8x-1=0 | | x^3-4x^2-8x+2=0 | | 4x^2-25x+20=-6x+8 | | b-5/3=2 | | 0=5b-30 | | 10(s-5)=-99 | | 0=56-30 | | z-6/9=7 | | x-8/9=2 | | f(-x)=7x+5 | | 60=2l+2(5w) | | 2(2+3y)-6y=4 | | 5(4+0.5w)+7w=1 |

Equations solver categories